After the Escuminac Disaster: Poverty and Paternalism in Miramichi Bay, New Brunswick - Rudin, Ronald (Acadiensis, 2023)
In June 1959, the fishing fleet leaving from the wharf at Escuminac in northeastern New Brunswick was struck by a hurricane resulting in the deaths of 35 men. The Escuminac Disaster was one of the worst work-related disasters in the province’s history, creating a significant challenge for dependents left behind with limited resources. In response, provincial leaders – both secular and religious – created the New Brunswick Fishermen’s Disaster Fund. The administrators of the fund, mostly well-to-do and English-speaking, exhibited great difficulty in understanding the survival strategies employed by families, all of whom were poor and many of whom were Acadian.